Terrorism and counter-terrorism criminological perspectives - Deflem, Mathieu (Elsevier, 2004)
Conferences, lectures, funding opportunities, and publications now all fully embrace terrorism and counter-terrorism as topics worthy of serious reflection and investigation among criminologists. The papers in this volume bring out the distinct contribution criminologists and criminological sociologists have to offer in the study of counter-terrorism from theoretical, methodological, and substantive viewpoints. The discussions of this title include a usefully broad variety of themes, including conceptual and theoretical perspectives in the criminology of terrorism; hate crimes and terrorism; civil liberties and the control of terrorism; terrorism, war and crime; state crime and terrorism; terrorism and transnational crime; the police dimensions of counter-terrorism; terrorism and the (international) court; terrorism and punishment; and, other issues. The specific criminological orientation of the book makes this volume stand out among others. Bringing together distinguished scholars to present these various themes, the volume hopes to bring a comprehensive and insightful state-of-the-art overview of terrorism and counter-terrorism as themes of criminological reflection.
Keywords: Terrorism.; Terrorism -- Prevention.; Terrorism, armed struggle.; Social Science -- Criminology.; Political Science -- Political Freedom & Security -- Terrorism.; elektronické knihy; Electronic books.; electronic books